2023
DOI: 10.3390/audiolres13030030
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Factors Affecting the Likelihood of Whether Individuals Would Purchase Cartilage Conduction Hearing Aids

Abstract: Cartilage conduction hearing aids (CC-HAs) are a novel type of hearing aid relying on cartilage conduction, the so-called third auditory conduction pathway. However, CC-HAs have only recently entered routine clinical use, and therefore data on their usefulness are lacking. The purpose of this study was to examine the possibility of assessing whether individual patients would show good adaptation to CC-HAs. Thirty-three subjects (41 ears in total) underwent a free trial of CC-HAs. Age, disease category, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Takai et al fitted CC hearing aids in 41 patients, 19 (65.9%) of whom purchased them after the trial [ 28 ]. They compared the clinical characteristics of the patients who purchased and did not purchase the hearing aids, and found that the rate of congenital canal stenosis or aural atresia was significantly higher in purchased cases than in the non-purchased cases.…”
Section: Benefits Of CC Hearing Aidsmentioning
confidence: 99%
“…Takai et al fitted CC hearing aids in 41 patients, 19 (65.9%) of whom purchased them after the trial [ 28 ]. They compared the clinical characteristics of the patients who purchased and did not purchase the hearing aids, and found that the rate of congenital canal stenosis or aural atresia was significantly higher in purchased cases than in the non-purchased cases.…”
Section: Benefits Of CC Hearing Aidsmentioning
confidence: 99%